2016
DOI: 10.15406/jpnc.2016.05.00174
|View full text |Cite
|
Sign up to set email alerts
|

Terminal 14q Deletion and Duplication with Gastrointestinal and Pulmonary Disease

Abstract: Terminal deletions of 14q are rare but have typical clinical findings whereas distal duplications of 14q are less well characterized. The combination of terminal deletion and distal duplication of 14q has only been reported once before. Neither terminal deletions nor duplications are consistently reported to have gastrointestinal or pulmonary manifestations. We report a terminal deletion and a distal inverted duplication of 14q in a patient with multiple anomalies; duodenal malrotation, feeding intolerance, ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Distal trisomy 14 is rarer than proximal trisomy 14, and full trisomy 14 most often causes stillbirth. Several cases involve DECIPHER’s genome database, with a brief phenotypic description ( ; accessed on 2 April 2021), and approximately 20 cases of pure 14q duplication are reported in the literature [ 14 , 28 , 31 , 34 , 39 , 40 , 42 , 44 , 45 , 47 , 48 , 49 ]. Despite the rarity of terminal 14q32 duplication, a distinct phenotype characterized by low birth weight, GR, DD/ID, hypotonia, and facial dysmorphisms has emerged.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Distal trisomy 14 is rarer than proximal trisomy 14, and full trisomy 14 most often causes stillbirth. Several cases involve DECIPHER’s genome database, with a brief phenotypic description ( ; accessed on 2 April 2021), and approximately 20 cases of pure 14q duplication are reported in the literature [ 14 , 28 , 31 , 34 , 39 , 40 , 42 , 44 , 45 , 47 , 48 , 49 ]. Despite the rarity of terminal 14q32 duplication, a distinct phenotype characterized by low birth weight, GR, DD/ID, hypotonia, and facial dysmorphisms has emerged.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the rarity of terminal 14q32 duplication, a distinct phenotype characterized by low birth weight, GR, DD/ID, hypotonia, and facial dysmorphisms has emerged. A systematic literature review of clinical features and frequencies in 45 reported cases with 14q duplication was conducted [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ] ( Supplementary Table S1 ). The unique phenotype was characterized by DD/ID (98%), low birth weight (60%), GR (36%) (blue bars in Figure 4 ), and facial dysmorphisms, including downslanting palpebral fissure, hyperteolorism, broad and/or flat nasal bridge, micrognathia, low-set ear, and sparse eyebrows and eyelashes (green bars in Figure 4 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations